2016
DOI: 10.5552/drind.2016.1529
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Common Hazelnut (Corylus avellana L.) Prunings for Pulp Production

Abstract: • For the purpose of this study, pulp and handseet were produced from common hazelnut (Coryllus avellana L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…In the study, 67% holocellulose, 57.4% alpha cellulose and 33% lignin were detected in HB material, which was evaluated for the first time in mushroom production. In a previous study cunducted by Gençer and Özgül 33 , holocellulose was found to be 82.07%, alpha cellulose 41.33, Lignin 15.89%, ash 0.72% and extractive substance 2.83% in the HB undegraded control sample. The amounts of holocellulose, alpha cellulose, lignin and ash in the HH undegraded control sample were determined as 55.1%, 34.5%, 35.1% and 8.22%, respectively, in a previous study cunducted by Güney 17 .…”
Section: Resultsmentioning
confidence: 80%
“…In the study, 67% holocellulose, 57.4% alpha cellulose and 33% lignin were detected in HB material, which was evaluated for the first time in mushroom production. In a previous study cunducted by Gençer and Özgül 33 , holocellulose was found to be 82.07%, alpha cellulose 41.33, Lignin 15.89%, ash 0.72% and extractive substance 2.83% in the HB undegraded control sample. The amounts of holocellulose, alpha cellulose, lignin and ash in the HH undegraded control sample were determined as 55.1%, 34.5%, 35.1% and 8.22%, respectively, in a previous study cunducted by Güney 17 .…”
Section: Resultsmentioning
confidence: 80%
“…Bu nedenle asli orman ağaçları dışında kalan ağaç, ağaççık ve çalı türlerinin hammadde potansiyelinin ortaya konması önem arz etmektedir. Daha önce yapılan çalışmalarda fındık odununun kraft yöntemi ile [1] ve soda yöntemi ile [2] kağıt hamuru üretimine uygunlukları belirlenmiştir. Benzer şekilde kivi budama artıklarının kağıt hamuru üretimine uygun olduğu bildirilmiştir [3].…”
unclassified